2022
DOI: 10.1177/09727531221108871
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Changes in Sickle Cell Disease: A Comprehensive Review

Abstract: Background: Sickle cell disease (SCD) is a type of hemoglobinopathy characterized by abnormal hemoglobin molecules, which includes numerous acute and chronic complications. Ischemic stroke, silent cerebral infarction, headache, and neurocognitive impairment are the most common neurological complications associated with SCD. Summary: Acute anemia because of SCD can cause cognitive impairments because of cerebral hypoxia. Cognitive abnormalities in SCD manifest in various aspects such as working memory, verbal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…In adulthood, the interest in cognition seems to decrease with sparse published studies as we can notice in the meta-analysis of Prussien et al on cognitive functioning in SCD patients (only 7 studies on SCD adult patients against 103 studies on children) [ 10 ]. This lack was also observed in Sahu’s review, where the majority of studies are on children or young adults [ 11 ]. However, this issue is also important, as the SCD population is getting older, and cognitive disorders make medical follow-up and social support more difficult.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In adulthood, the interest in cognition seems to decrease with sparse published studies as we can notice in the meta-analysis of Prussien et al on cognitive functioning in SCD patients (only 7 studies on SCD adult patients against 103 studies on children) [ 10 ]. This lack was also observed in Sahu’s review, where the majority of studies are on children or young adults [ 11 ]. However, this issue is also important, as the SCD population is getting older, and cognitive disorders make medical follow-up and social support more difficult.…”
Section: Introductionmentioning
confidence: 74%
“…In a recent comprehensive review, Sahu et al reported mainly dysexecutive disorders with learning difficulties, working memory disorders and attentional disorders in adults and children, with dramatic consequences both in their daily and professional lives, but also in terms of therapeutic follow-up. Cognitive disorders are more important in patients with cerebro-vascular disorders like stroke and/or SCI or vasculopathy [ 11 , 12 ]. However, cognitive disorders were depicted in adult patients with SCD, even in the absence of overt neurological events, in a neuroimaging study [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silent cerebral infarcts detected on MRI are common in SCD patients and are associated with cognitive deficits even without overt stroke symptoms [82,88]. Cognitive impairments after an overt stroke include issues with language, processing speed, memory, and executive functions [87,89]. However, long-term studies on cognitive outcomes are also lacking.…”
Section: Clinical Features Of Stroke In Patients With Scdmentioning
confidence: 99%
“…A cooperative study of SCD found that patients with a TIA had a 10-fold increased risk of subsequent IS compared to those without a TIA history [57,82]. Chronic transfusion programs after TIA have significantly reduced stroke risk, indicating TIA's importance as a warning sign [85,89,91].…”
Section: Potential Risk Elements For Stroke In Patients With Scdmentioning
confidence: 99%
“…However, no association between TCD and IQ was found in older SCA children [ 8 , 9 ]. Investigations into MRI abnormalities have reported an association between IQ and SCI or lacunae, but the association diminished when age was added as a covariate [ 10 ]. Cognitive decline in sickle cell anaemia patients persisted even in the absence of SCI [ 4 ].…”
Section: Introductionmentioning
confidence: 99%